2024
DOI: 10.1002/advs.202401889
|View full text |Cite
|
Sign up to set email alerts
|

Designing Reliable Cathode System for High‐Performance Inorganic Solid‐State Pouch Cells

Shuying Wang,
Sheng Liu,
Wei Chen
et al.

Abstract: All‐solid‐state batteries (ASSBs) based on inorganic solid electrolytes fascinate a large body of researchers in terms of overcoming the inferior energy density and safety issues of existing lithium‐ion batteries. To date, the cathode designs in the ASSBs achieve remarkable achievements, adding the urgency of scaling up the battery system toward inorganic solid‐state pouch cell configuration for the application market. Herein, the recent developments of cathode materials and the design considerations for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 169 publications
(216 reference statements)
0
1
0
Order By: Relevance
“…All-solid-state lithium-ion batteries (ASSLIBs) employing inorganic solid electrolytes (SEs) are acknowledged to enable a more stable (electro)­chemo-mechanical environment for those volume-changing electrode materials than liquid LIBs. For instance, SEs cannot freely flow to wet the newly exposed electrode interfaces, which favors stable SEI formation. Among all investigated SEs, sulfide electrolytes exhibit favorable mechanical ductility and the highest room-temperature ionic conductivity comparable to or exceeding liquid electrolytes. , Recent advances have witnessed excellent compatibility of alloy-type anodes with sulfide SEs. Some typical alloy anodes (e.g., Si, Al, or their lithiated forms) used in sulfide ASSLIBs have achieved far better long-term cycling stability than liquid LIBs. Based on theoretical estimation, McDowell et al have identified that both gravimetric/volumetric energy densities of ASSLIBs with some alloy anodes are far beyond those of commercial graphite LIBs, even comparable to those evaluated of the Li-metal batteries using excess Li …”
Section: Introductionmentioning
confidence: 99%
“…All-solid-state lithium-ion batteries (ASSLIBs) employing inorganic solid electrolytes (SEs) are acknowledged to enable a more stable (electro)­chemo-mechanical environment for those volume-changing electrode materials than liquid LIBs. For instance, SEs cannot freely flow to wet the newly exposed electrode interfaces, which favors stable SEI formation. Among all investigated SEs, sulfide electrolytes exhibit favorable mechanical ductility and the highest room-temperature ionic conductivity comparable to or exceeding liquid electrolytes. , Recent advances have witnessed excellent compatibility of alloy-type anodes with sulfide SEs. Some typical alloy anodes (e.g., Si, Al, or their lithiated forms) used in sulfide ASSLIBs have achieved far better long-term cycling stability than liquid LIBs. Based on theoretical estimation, McDowell et al have identified that both gravimetric/volumetric energy densities of ASSLIBs with some alloy anodes are far beyond those of commercial graphite LIBs, even comparable to those evaluated of the Li-metal batteries using excess Li …”
Section: Introductionmentioning
confidence: 99%